2020
DOI: 10.31234/osf.io/5sw6m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From many to (n)one: Meditation and the plasticity of the predictive mind

Abstract: How profoundly can humans change their own minds? In this paper we offer a unifying account of meditation under the predictive processing view of living organisms. We start from relatively simple axioms. First, the brain is an organ that serves to predict based on past experience, both phylogenetic and ontogenetic. Second, meditation serves to bring one closer to the here and now by disengaging from anticipatory processes. We propose that practicing meditation therefore gradually reduces predictive processing,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 115 publications
(228 reference statements)
5
46
0
Order By: Relevance
“…Of note, in mechanistic terms, these qualitative insights seem to be parsimonious with recent discussions of meditation within the predictive processing and active inference frameworks [ 82 , 83 , 84 ], where the release of attentional focus would correspond to a leveling of (ingrained and biased) precision weights, resulting in a (partial) suspension of ordinary self-evidencing (i.e. suspending the enactment of generative models [ 85 ]).…”
Section: Discussionsupporting
confidence: 70%
“…Of note, in mechanistic terms, these qualitative insights seem to be parsimonious with recent discussions of meditation within the predictive processing and active inference frameworks [ 82 , 83 , 84 ], where the release of attentional focus would correspond to a leveling of (ingrained and biased) precision weights, resulting in a (partial) suspension of ordinary self-evidencing (i.e. suspending the enactment of generative models [ 85 ]).…”
Section: Discussionsupporting
confidence: 70%
“…We hypothesized that the oddball response (i.e., a prediction error signal) would be reduced in the meditation population relative to the controls. It has more recently been suggested that the oddball response may be sufficiently evolutionarily ingrained to remain unmalleable by meditation training [ 96 ]. Here, we observe decreased TPJ responsively to oddball stimuli with a small (0.34) effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Such investigation, describing the conditions constitutive of desirable states of dissolution, could have important implications for teachers of mindfulness and possibly also clinicians. These considerations, sometimes addressed by mindfulness teachers [90,91], are becoming increasingly relevant due to the phenomenological similarities between some psychopathologies (depersonalization in particular) 11 Of note, in mechanistic terms, these qualitative insights seem to be parsimonious with recent discussions of meditation within the predictive processing and active inference frameworks [83][84][85], where the release of attentional focus would correspond to a leveling of (ingrained and biased) precision weights, resulting in a (partial) suspension of ordinary self-evidencing (i.e. suspending the enactment of generative models [86]).…”
Section: The Relation Of Affect and Sense Of Boundariesmentioning
confidence: 97%